Lithic technologies in sedentary societies - Horowitz, Rachel A. (Archaeologist); McCall, Grant S. (Louisville : University Press of Colorado, 2019)
"Examining lithic technology in sedentary societies around the world and showcasing information that in-depth, cutting-edge, lithic analytical techniques provides. Highlighting important contributions to the field of lithics and how they can improve the study of sedentary Mesoamerican societies, as well as other ancient societies around the world"--Provided by publisher
Lithics in sedentary societies : themes, methods, and directions / Rachel A. Horowitz and Grant S. McCall -- Urban lithics : the role of stone tools in the Indus civilization and at Harappa / Mary A. Davis -- The importance of being ad hoc : patterns and implications of expedient lithic production in the Bronze Age in Israel / Francesca Manclossi and Steven A. Rosen -- Leaving no stone unturned : expedient lithic production among preclassic households of San Estevan, Belize and K'o and Hamontún, Guatemala / Jason S.R. Paling -- The economic organization of the extraction and production of utilitarian chert tools in the Mopan Valley, Belize / Rachel A. Horowitz -- Chert at Chalcatzingo : implications of knapping strategies and technological organization for formative economics / Grant S. McCall, Rachel A. Horowitz, Dan M. Healan, and David C. Grove -- Unraveling sociopolitical organization using lithic data : a case study from an agricultural society in the American Southwest / Fumiyasu Arakawa -- Using portable X-ray fluorescence (pXRF) to source Burlington chert from the Carson site, 22CO505, Coahoma County, Mississippi / Jayur Madhusudan Mehta, Grant S. McCall, Theodore Marks, and James Enloe -- Stone age economics : efficiency, blades, specialization, and obsolescence / John C. Whittaker.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 13, 2019).
eBooks on EBSCOhost
Keywords: Stone implements -- Analysis; Tools, Prehistoric -- Analysis; Prehistoric peoples -- Antiquities; Economics, Prehistoric; Excavations (Archaeology); Outils de pierre -- Analyse; Outils préhistoriques -- Analyse; Économie préhistorique.; Fouilles (Archéologie); excavation (process); HISTORY -- Ancient -- General; SOCIAL SCIENCE -- General; Economics, Prehistoric; Excavations (Archaeology); Prehistoric peoples -- Antiquities; Stone implements -- Analysis; Tools, Prehistoric -- Analysis; Electronic books